2018
DOI: 10.1108/dlo-01-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality: a new imperative in Indian manufacturing sector

Abstract: Purpose This paper aims to illustrate the need for workplace spirituality (WPS) through the planned implementation of strategies in the Indian manufacturing sector. Design/methodology/approach This paper is a viewpoint based on literature review. Findings WPS is useful for reducing employee turnover as well as increasing satisfaction, commitment, and engagement among employees. Employees feel empowered if they get ample opportunities and challenging tasks to grow in a positive environment. Originality/va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…For this reason, the manufacturing employers focus more in making their employees marketable and advanced. Competent employees get ample opportunities of showcasing their talent; hence, they perceive their work to be meaningful (Singh and Rangnekar, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the manufacturing employers focus more in making their employees marketable and advanced. Competent employees get ample opportunities of showcasing their talent; hence, they perceive their work to be meaningful (Singh and Rangnekar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Employees also feel that when their psychological contract is breached, it leads to a feeling of lack of meaningfulness in work and decreased commitment levels (Jos et al , 2017). Singh and Rangnekar (2018) suggested certain strategies to increase meaningfulness in work, which is visible in the association with psychological contract between employees and employers and contributes toward determining the level of employees' satisfaction in the Indian manufacturing sector. These strategies are executed to improve positivity in order to achieve targets, encourage employee involvement and participation, validate employee contribution in task accomplishment and to abide by ethical HR practices while dealing with employees.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees are made to feel valuable by providing them with legitimate responsibilities and challenging tasks. This process makes them more prone to show their real capabilities and helps in finding meaningfulness in work (Singh and Rangnekar, 2018). Providing more responsibilities is one of the tools that employers use in the job design concept through which employees have more opportunities to handle different types of work and to prove their worth.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research says that people who are found to be more aware of their thoughts and actions are said to be mindful and more likely to experience positive emotions such as high concentration level, special energy and passion at work (Alidina, 2020; Nirban, 2018). Mindfulness has emerged as a concept that can help employees to increase their concentration levels in difficult work conditions and become more productive, especially in manufacturing settings (Singh and Rangnekar, 2018). Organizations are also striving hard to create a positive environment by connecting their employees through mindful practices; this in turn permits them to seek meaningfulness in work and achieve a transcendence state (Petchsawang and Duchon, 2012; Petchsawang and McLean, 2017; Paul et al , 2019a).…”
Section: Introductionmentioning
confidence: 99%